Role of Na+ and Li+ in thiomethylgalactoside transport by the melibiose transport system of Escherichia coli. - Lopilato, J (1978)
Thiomethyl-beta-galactoside (TMG) accumulation via the melibiose transport system was studied in lactose transport-negative strains of Escherichia coli. TMG uptake by either intact cells or membrane vesicles was markedly stimulated by Na+ or Li+ between pH 5.5 and 8. The Km for uptake of TMG was approximately 0.2 mM at an external Na+ concentration of 5 mM (pH 7). The alpha-galactosides, melibiose, methyl-alpha-galactoside, and o-nitrophenyl-alpha-galactoside had a high affinity for this system whereas lactose, maltose and glucose had none. Evidence is presented for Li+-TMG or Na+-TMG cotransport.